Common datastream permutations of animal social network data are not appropriate for hypothesis testing using regression models. Issue 2 (18th October 2020) - Weiss, Michael N.; Franks, Daniel W.; Brent, Lauren J. N.; Ellis, Samuel; Silk, Matthew J.; Croft, Darren P.
Abstract: Social network methods have become a key tool for describing, modelling and testing hypotheses about the social structures of animals. However, due to the non‐independence of network data and the presence of confounds, specialised statistical techniques are often needed to test hypotheses in these networks. Datastream permutations, originally developed to test the null hypothesis of random social structure, have become a popular tool for testing a wide array of null hypotheses in animal social networks. In particular, they have been used to test whether exogenous factors are related to network structure by interfacing these permutations with regression models. Here, we show that these datastream permutations typically do not represent the null hypothesis of interest to researchers interfacing animal social network analysis with regression modelling, and use simulations to demonstrate the potential pitfalls of using this methodology. Our simulations show that, if used to indicate whether a relationship exists between network structure and a covariate, datastream permutations can result in extremely high type I error rates, in some cases approaching 50%. In the same set of simulations, traditional node‐label permutations produced appropriate type I error rates (~5%). Our analysis shows that datastream permutations do not represent the appropriate null hypothesis for these analyses. We suggest that potential alternatives to this procedure may be found in regarding the problems of non‐independence of network data and unreliability of observations separately. If biases introduced during data collection can be corrected, either prior to model fitting or within the model itself, node‐label permutations then serve as a useful test for interfacing animal social network analysis with regression modelling.